Ethnic and Immigrant Variations in the Time Trends of Dementia and Parkinsonism. (12th November 2021) - Wong, Jessica J.; Kwong, Jeffrey C.; Tu, Karen; Butt, Debra A.; Wilton, Andrew S.; Shah, Baiju R.; Murray, Brian J.; Kopp, Alexander; Chen, Hong
ABSTRACT: Objective: We assessed long-term incidence and prevalence trends of dementia and parkinsonism across major ethnic and immigrant groups in Ontario. Methods: Linking administrative databases, we established two cohorts (dementia 2001–2014 and parkinsonism 2001–2015) of all residents aged 20 to 100 years with incident diagnosis of dementia (N = 387, 937) or parkinsonism (N = 59, 617). We calculated age- and sex-standardized incidence and prevalence of dementia and parkinsonism by immigrant status and ethnic groups (Chinese, South Asian, and the General Population). We assessed incidence and prevalence trends using Poisson regression and Cochran–Armitage trend tests. Results: Across selected ethnic groups, dementia incidence and prevalence were higher in long-term residents than recent or longer-term immigrants from 2001 to 2014. During this period, age- and sex-standardized incidence of dementia in Chinese, South Asian, and the General Population increased, respectively, among longer-term immigrants (by 41%, 58%, and 42%) and long-term residents (28%, 7%, and 4%), and to a lesser degree among recent immigrants. The small number of cases precluded us from assessing parkinsonism incidence trends. For Chinese, South Asian, and the General Population, respectively, prevalence of dementia and parkinsonism modestly increased over time among recent immigrants but significantly increased among longer-term immigrants (dementia: 134%, 217%, and 117%; parkinsonism: 55%, 54%, and 43%) and long-term residents (dementia: 97%, 132%, and 71%; parkinsonism: 18%, 30%, and 29%). Adjustment for pre-existing conditions did not appear to explain incidence trends, except for stroke and coronary artery disease as potential drivers of dementia incidence. Conclusion: Recent immigrants across major ethnic groups in Ontario had considerably lower rates of dementia and parkinsonism than long-term residents, but this difference diminished with longer-term immigrants.